An Account of Indigenous Fishing Gears of Narmada Estuary, Gujarat, India - BHAKTA, D; MEETEI, W A; VAISAKH, G; KAMBLE, S; CHANU, T N; DAS, S K (Journal of the Indian Society of Coastal Agricultural Research, 2017)
A wide variety of traditional fishing gears are employed throughout the Narmada estuarine region owing to its rich fish biodiversity, but with certain limitations. Documentation of such devices is a need for scientific improvement, and for better socio-economic upliftment of the fishers involved. A total of 12 numbers of traditional fishing techniques was encountered during the study period (2014-15). Catch per unit effort from all of the fishing devices are reportedly declining over the years due to over fishing, habitat destruction, pollution etc. Reduction in fish catching efficiency, income generation through fishing activities gradually decreasing resulting in reduction of active fishermen population. The present paper is an attempt to document all kinds of fishing gears that evolved through indigenous technical knowledge (ITK) used in the Narmada estuary.